A genotype–phenotype association approach to reveal thermal adaptation in Daphnia galeata. Issue 1 (January 2017) - Herrmann, Maike; Henning‐Lucass, Nicole; Cordellier, Mathilde; Schwenk, Klaus
GRAPHICAL ABSTRACT: We showed significant temperature effects on fitness‐related life‐history traits. No direct genotype–phenotype relation was found, but significant GxE interactions that might reflect a contribution of marker loci to quantitative life‐history traits. Abstract: Altering thermal environments impose strong selection pressures on organisms, whose local persistence depends on adaptive phenotypic plastic and genetic responses. Thus far, adaptive change is monitored using phenotypic shifts or molecular markers, although inevitable obstacles are inherent in both methods. In order to circumvent these, it is necessary to find a causal link between adaptive alleles and fitness. Combining both approaches by linking genetic analyses and life‐history measurements, a potential genotype–phenotype relationship can be assessed and adaptation at the molecular level demonstrated. For our study, clonal lineages of the freshwater keystone species D. galeata from seven different populations distributed along a latitudinal gradient across Europe were tested for local thermal adaptation in common garden experiments. Fitness‐related life‐history responses were quantified under different thermal regimes and experimental clones were genotyped at three candidate gene marker loci to investigate a potential genotype–phenotype association. The analyses of the life‐history data showed a significant temperature effect on several fitness‐related life‐history traits recorded in our experiments. However, we could not detect evidence for a direct association at neither candidate gene locus between genotypes and life‐history traits. The observed phenotypic shifts might therefore not be based on the tested marker loci EA, M and TF, or in general not coding sequence‐based and thus rather reveal phenotypic plasticity in response to thermal variation. Nonetheless, we revealed significant genotype by environment (GxE) interactions at all tested loci, potentially reflecting a contribution of marker loci to certain life‐history trait values and contribution of multiple genetic loci to phenotypic traits.